The Engineer in the Industrial Corporation - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1973)
This article reviews "The Engineer in the Industrial Corporation" by Richard R. Ritti.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z